The light-harvesting chlorophyll a/b-binding proteins of photosystem II family members are responsible for temperature sensitivity and leaf color phenotype in albino tea plant - Jing-Jing Ye; Xin-Yi Lin; Zi-Xian Yang; Ying-Qi Wang; Yue-Rong Liang; Kai-Rong Wang; Jian-Liang Lu; Peng Lu; Xin-Qiang Zheng (Journal of Advanced Research)
Introduction: Light-harvesting chlorophyll a/b-binding (LHCB) protein complexes of photosystem II are integral to the formation of thylakoid structure and the photosynthetic process. They play an important role in photoprotection, a crucial process in leaf development under low-temperature stress. Nonetheless, potential key genes directly related to low-temperature response and albino phenotype have not been precisely identified in tea plant. Moreover, there are no studies simultaneously investigating multiple albino tea cultivars with different temperature sensitivity. Objectives: The study aimed to clarify the basic characteristics of CsLHCB gene family members, and identify critical CsLHCB genes potentially influential in leaf color phenotypic variation and low-temperature stress response by contrasting green and albino tea cultivars. Concurrently, exploring the differential expression of the CsLHCB gene family across diverse temperature-sensitive albino tea cultivars. Methods: We identified 20 putative CsLHCB genes according to phylogenetic analysis. Evolutionary relationships, gene duplication, chromosomal localization, and structures were analyzed by TBtools; the physiological and biochemical characteristics were analyzed by protein analysis websites; the differences in coding sequences and protein accumulation in green and albino tea cultivars, gene expression with maturity were tested by molecular biology technology; and protein interaction was analyzed in the STRING database. Results: All genes were categorized into seven groups, mapping onto 7 chromosomes, including three tandem and one segmental duplications. They all own a conserved chlorophyll A/B binding protein domain. The expression of CsLHCB genes was tissue-specific, predominantly in leaves. CsLHCB5 may play a key role in the process of leaf maturation and senescence. In contrast to CsLHCB5, CsLHCB1.1, CsLHCB2, and CsLHCB3.2 were highly conserved in amino acid sequence between green and albino tea cultivars. In albino tea cultivars, unlike in green cultivars, the expression of CsLHCB1.1, CsLHCB1.2, and CsLHCB2 was down-regulated under low-temperature stress. The accumulation of CsLHCB1 and CsLHCB5 proteins was lower in albino tea cultivars. Greater accumulation of CsLHCB2 protein was detected in RX1 and RX2 compared to other albino cultivars. Conclusions: CsLHCB1.1, CsLHCB1.2, and CsLHCB2 played a role in the response to low-temperature stress. The amino acid sequence site mutation of CsLHCB5 would distinguish the green and albino tea cultivars. The less accumulation of CsLHCB1 and CsLHCB5 had a Chl influence on albino leaves. Albino cultivars more sensitive to temperature exhibited lower CsLHCB gene expression. CsLHCB2 may serve as an indicator of temperature sensitivity differences in albino tea cultivars. This study could provide a reference for further studies of the functions of the CsLHCB family and contribute to research on the mechanism of the albino in tea plant.